1990
DOI: 10.2307/622670
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Migration: The Example of Ireland in the Nineteenth Century

Abstract: "A classic case where out-migration interacted with many other geographical phenomena is provided by rural Ireland in the nineteenth century. The apparent turning point was the Great Famine of the 1840s, but the areas with the greatest suffering from starvation did not necessarily show the greatest population decline, suggesting that other forces were active. Considerable economic and social changes were already taking place before the Famine: fertility was being reduced, later marriage was becoming establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The following extracts suggest that individual migrants undergo change: change that makes returning to the home community difficult. As Johnson (1990) reports 'they become foreigners in their own community' (p. 274). Laura, who had been away for almost 20 years, returned to Lewis with her family but later left the island again:…”
Section: Return Migration: Motivations Experiences and Business Creamentioning
confidence: 95%
“…The following extracts suggest that individual migrants undergo change: change that makes returning to the home community difficult. As Johnson (1990) reports 'they become foreigners in their own community' (p. 274). Laura, who had been away for almost 20 years, returned to Lewis with her family but later left the island again:…”
Section: Return Migration: Motivations Experiences and Business Creamentioning
confidence: 95%
“…R esearch on rural youth and place attachment has made critical contributions to our understanding of young people's mobility, their out-migration from or reasons for staying in rural communities. Some of the most covered topics within rural youth research have been the influence of education and social class in migration decision-making processes (Jamieson 2000;N ı Laoire 2000;Andersen 2017), the demographic, social and economic causes and impacts of migration -for the migrants leaving as well as for the communities that are left behind (Stockdale 2004;Argent and Walmsley 2008;Gibson and Argent 2008), the importance of prior migration by family members (Johnson 1990;Stockdale 2002), life-course perspectives on migration (Niedomysl 2010;Aner and Hansen 2014;Stockdale and Catney 2014) and how more women than men tend to leave rural communities (Båtevik 2001;Bjarnason and Thorlindsson 2006;Faber et al 2015). Several studies have demonstrated significant power imbalances between rural and urban (Vanderbeck and Dunkley 2003;Jensen 2012;Farrugia 2016), and exposed how rural-to-urban migration represents not only a geographical mobility, but also a social mobility, where migration is a way to move forwards and pursue a career (Green 1999;N ı Laoire 2000;Corbett 2007;Argent and Walmsley 2008;Beck et al 2009;Trell et al 2012;Nugin 2014;Bloksgaard et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research on rural youth and place attachment has made critical contributions to our understanding of young people's mobility, their out‐migration from or reasons for staying in rural communities. Some of the most covered topics within rural youth research have been the influence of education and social class in migration decision‐making processes (Jamieson ; Ní Laoire ; Andersen ), the demographic, social and economic causes and impacts of migration – for the migrants leaving as well as for the communities that are left behind (Stockdale ; Argent and Walmsley ; Gibson and Argent ), the importance of prior migration by family members (Johnson ; Stockdale ), life‐course perspectives on migration (Niedomysl ; Aner and Hansen ; Stockdale and Catney ) and how more women than men tend to leave rural communities (Båtevik ; Bjarnason and Thorlindsson ; Faber et al . ).…”
Section: Introductionmentioning
confidence: 99%